Urban railways and the civil engineer proceedings of a conference organized by the Institution of Civil Engineers and held in London 30 September - 2 October 1987. (Thomas Telford, 1987)
Throughout the world, the urban railway has become prominent as a transport facility for large mobile populations in big cities. This volume covers planning, design, construction and maintenance of all categories of urban railways - metros, light rail and heavy rail.